PERAN LURAH SEBAGAI MOTIVATOR DALAM MENEGAKKAN DISIPLIN WAKTU APARATUR PADA KANTOR KELURAHAN AGUNG KECAMATAN TANJUNG KABUPATEN TABALONG - Suriadi; Rahmi Hayati (p3m.stiatabalong.ac.id, 2022)
The purpose of this study was to determine the role of the village head as a motivator in enforcing apparatus time discipline at the Agung Village office. The method used in this research is a qualitative descriptive approach. The descriptive approach is part of the explanation or writing of each variable, by describing the situation or events that occur in the object of research. While the qualitative approach is research that can produce descriptive data in the form of written or spoken words from people and observable behavior who become informants in the research. Data collection techniques used in this study are observation data collection techniques, interview data collection techniques, and documentation data collection techniques. The conclusion results from the Recapitulation of the Role of the village head as a Motivator in Enforcing Time Discipline of Apparatuses at the Agung Village Office, Tanjung sub-district, Tabalong Regency on the Motivator of Spirit Indicator is Role play, the conclusion results on the Fostering Indicator are Role play and the conclusion results on the Indicator of Giving Influence are Role Enough. Then the results obtained from the research on the Role of the village head as a Motivator in Enforcing Time Discipline of Apparatuses at the Agung village Office, Tanjung Sub-district, Tabalong Regency, can be concluded that they have a role, this can be seen from the results of the interview recapitulation of 5 village officials conducted by researchers at the Agung village Office. Keywords: Role, Time Discipline.